Pengendalian Kualitas Kertas Dengan Menggunakan Statistical Process Control di Paper Machine 3 - Devani, Vera; Wahyuni, Fitri (Universitas Muhammadiyah Surakarta, 2016)
Purpose of this research is to determine types and causes of defects commonly found in Paper Machine 3 by using statistical process control (SPC) method. Â Statistical process control (SPC) is a technique for solving problems and is used to monitor, control, analyze, manage and improve products and processes using statistical methods. Â Based on Pareto Diagrams, wavy defect is found as the most frequent defect, which is 81.7%. Â Human factor, meanwhile, is found as the main cause of defect, primarily due to lack of understanding on machinery and lack of training both leading to errors in data input.